2006
DOI: 10.1007/s00280-006-0357-8
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of the immunosuppressive agents cyclosporin A, tacrolimus and sirolimus on drug transport by multidrug resistance proteins

Abstract: CsA, tacrolimus and sirolimus modulate drug transport by Pgp, MRP-1 and BCRP and CsA and sirolimus modulate drug transport by LRP at concentrations that differ from immunosuppressive concentrations and maximum tolerated concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(37 citation statements)
references
References 40 publications
1
35
0
Order By: Relevance
“…In fact, rapamycin and tacrolimus affected Pgp activity but they did not modulate Pgp function at pre-established doses. Similarly to what was previously reported by Pawarode and collegues (25) here, we show that CsA seems to be a broadspectrum MDR modulator impairing drug transport at the clinically achievable concentration of 2.5 µM, tacrolimus enhanced cellular drug uptake at 1 µM, but not at its clinically achievable concentration (0.1 µM). Rapamycin exerts the optimal effect of enhancing cellular drug uptake at 2.5 µM, but it was not effective at its clinically achievable concentration of 0.25 µM.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In fact, rapamycin and tacrolimus affected Pgp activity but they did not modulate Pgp function at pre-established doses. Similarly to what was previously reported by Pawarode and collegues (25) here, we show that CsA seems to be a broadspectrum MDR modulator impairing drug transport at the clinically achievable concentration of 2.5 µM, tacrolimus enhanced cellular drug uptake at 1 µM, but not at its clinically achievable concentration (0.1 µM). Rapamycin exerts the optimal effect of enhancing cellular drug uptake at 2.5 µM, but it was not effective at its clinically achievable concentration of 0.25 µM.…”
Section: Discussionsupporting
confidence: 65%
“…Stimulated cells are exposed to allogeneic T-cell depleted lymphocytes. Drug concentrations were obtained from Pawarode et al choosing those in the upper level (25).…”
Section: Isolation Of Peripheral Blood Lymphocytesmentioning
confidence: 99%
“…Thus, this result implies that the autophagic machinery downstream of Beclin1-dependent induction was not a rate-limiting factor. On the other hand, rapamycin has been documented to modulate the transport function of Pglycoprotein, thereby acting as an agent that reverses the multidrugresistance phenotype (Arceci et al, 1992;Pawarode et al, 2007;Pop et al, 2009). Our results show that, although rapamycin inhibits P-glycoprotein expression in Ras-NIH3T3/Mdr cells, rapamycin has no effect on susceptibility to chemotherapeutic agents such as paclitaxel.…”
Section: Discussionmentioning
confidence: 99%
“…Rapamycin (sirolimus), one of the main mTOR inhibitors used in clinical trials (Hartford and Ratain, 2007), has shown significant chemotherapeutic antitumor activity in various models (Kim et al, 2008;Weppler et al, 2007). Moreover, studies have established that rapamycin can downregulate and disable the P-glycoprotein pump (Pop et al, 2009) and enhance cellular drug uptake in cells overexpressing P-glycoprotein (Pawarode et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, for a 70-kg subject, taking the volume of the gastrointestinal tract (3-5 l) into consideration (Egashira et al, 2004), the concentration of FK506 in the intestinal surface would be 1-3.5 mg/ml. In addition, a previous study (Pawarode et al, 2007) showed that 1 mM (about 0.8 mg/ml) of FK506 could enhance cellular drug uptake in cells overexpressing P-gp, multidrug resistance-associated protein 1 (MRP-1), or Breast cancer resistance-related protein (BCRP). Thus, to limit the inhibition effect of FK506 on P-gp activity and better mimic the clinical herb-drug interaction, the concentration of FK506 used in the transport experiment was set at 1 mg/ml (Qin et al, 2010b).…”
Section: Discussionmentioning
confidence: 99%